2021
DOI: 10.1073/pnas.2100901118
|View full text |Cite
|
Sign up to set email alerts
|

Herded and hunted goat genomes from the dawn of domestication in the Zagros Mountains

Abstract: The Aceramic Neolithic (∼9600 to 7000 cal BC) period in the Zagros Mountains, western Iran, provides some of the earliest archaeological evidence of goat (Capra hircus) management and husbandry by circa 8200 cal BC, with detectable morphological change appearing ∼1,000 y later. To examine the genomic imprint of initial management and its implications for the goat domestication process, we analyzed 14 novel nuclear genomes (mean coverage 1.13X) and 32 mitochondrial (mtDNA) genomes (mean coverage 143X) from two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 64 publications
4
35
0
1
Order By: Relevance
“…In addition, the highest average F ROH (26.39%) was observed in BEZ. This is in line with previous studies reporting the highest rates of extreme F ROH;5 Mb in modern wild bezoar from Iran [ 3 ] and lower levels of diversity compared to domesticated goats [ 26 ]. The differences in the genetic make-up of Bezoar goats and domesticated purebred goats and the high genomic inbreeding in BEZ needs further clarification by sampling more wild Bezoar goats from different geographic origins.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the highest average F ROH (26.39%) was observed in BEZ. This is in line with previous studies reporting the highest rates of extreme F ROH;5 Mb in modern wild bezoar from Iran [ 3 ] and lower levels of diversity compared to domesticated goats [ 26 ]. The differences in the genetic make-up of Bezoar goats and domesticated purebred goats and the high genomic inbreeding in BEZ needs further clarification by sampling more wild Bezoar goats from different geographic origins.…”
Section: Discussionsupporting
confidence: 93%
“…The domestication of goat ( Capra hircus ) started 11,000 years ago in the fertile crescent [ 1 , 2 ]. Based on archaeological caprine remains (around 8200 years BC) from the Zagros mountains (eastern Fertile Crescent, western Iran) and by combining archaeozoological and archaeogenomic approaches, Daly et al [ 3 ] reported the existence of two distinct clusters of goats: one with domestic affinity and one with wild affinity. These findings indicate, that these goats from the late ninth/early eighth millennium BC were genetically diverse, already distinct from wild goats and ancestral to later domestic goats [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent aDNA analysis of early managed goats in the central Zagros suggests some genetic divergence from local wild populations, but without a genetic bottleneck or phenotypic differentiation (e.g. coat pigmentation) from wild goats (Daly et al 2021). Goat management appears in adjacent lowland regions in the 8th millennium BCE (Saña Segui 2000), further reflecting the agency of goats whose physiology and disease ecology promoted transhumant co-residence with humans.…”
Section: Human and Non-human Agencymentioning
confidence: 99%
“…Goat management appears in adjacent lowland regions in the 8th millennium BCE (Saña Segui 2000), further reflecting the agency of goats whose physiology and disease ecology promoted transhumant co-residence with humans. The ecological and behavioural patterns of goats prevented them from being translocated to lowland regions for more than a millennium, at which point they became morphologically distinct in the absence of gene flow with wild populations (Daly et al 2021).…”
Section: Human and Non-human Agencymentioning
confidence: 99%